Kompetensi Aparatur Desa, Komitmen Organisasi, Kejelasan Sasaran Anggaran dan Akuntabilitas Pengelolaan Dana Desa - Suryani, Ni Made; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi, 2021)
This study aims to determine the effect of village apparatus competence, organizational commitment, clarity of budget targets on the accountability of village fund management. The sample of this research was 30 villages in Buleleng Regency with the number of respondents as many as 120 people. The method of determining the sample using purposive sampling method and data collection using a questionnaire. The data analysis technique used is multiple linear regression analysis. The test results of this study indicate that the competence of village officials, organizational commitment, and clarity of budget targets have a positive influence on the accountability of village fund management. The results of this study prove empirically that the stewardship theory and compliance theory have been confirmed and are able to explain the effect of village apparatus competence, organizational commitment, and clarity of budget targets on accountability of village fund management. Keywords: Village Apparatus Competence; Organizational Commitment; Clarity of Budget Targets; Accountability.